Respostas

2014-04-17T22:37:07-03:00
(x - 5)² = 1    Fatorando: => x² - 10x + 25 = 1

(2x - 4)² = 0 Fatorando também: => 4x² - 16x + 16 = 0
2014-04-17T22:49:05-03:00
(x - 5)² = 1 
(x)² -2 . x . (-5) -(5)² = 1
x² + 10x + 25= 1
x² + 10x + 25 - 1=0
x² + 10x +24 = 0
a=1  b=10  c=24

Δ=b² - 4.a.c
Δ=(10)² - 4.1.24
Δ=100 - 96
Δ= 4

X= -b +- √Δ
         2.a

X= -10 +- √4
         2 . 1

X= -10 +- 2
          2

X'= -10 - 2 = -12  = - 6
         2          2

X''= -10 + 2 = -8  = - 4         S ={ - 4, - 6 }
           2        2




(2x - 4)² = 0
(2x)² -2 .2x.(-4) - (4)²=0
4x² + 16x - 16 = 0
a=4   b=16   c= -16

Δ= b² - 4.a.c
Δ=(16)² - 4.4.(-16)
Δ=256 + 256
Δ=512  não possui raiz exata